GENETIC VARIABILITY OF Gallibacterium anatis STRAINS ISOLATED FROM PERUVIAN COMMERCIAL BIRDS WITH RESPIRATORY INFECTIONS - Mendoza A., Karina (2014)
The purpose of this study was to determine the genetic variability of strains of Gallibacterium anatis isolated in commercial poultry with respiratory symptoms from Arequipa (2), Ica (3), La Libertad (27), Lima (62), Madre de Dios (1) and Ucayali (1), collected from 2007 to 2011. Strains were typified by carbohydrate fermentation tests and sensitivity to nine antimicrobials. The genetic variability of these strains was determined by ERIC-PCR, after identification by PCR using specific primers. The analysis of carbohydrate fermentation profiles corresponded to 10 biovars, all of which were found in Lima and 45.8% of the strains belonged to biovar 4. Concerning antimicrobial susceptibility, 40.8% of strains were resistant to all antimicrobials studied, while 94.8 and 95.8% were resistant to enrofloxacin and ciprofloxacin. By ERIC-PCR 24 DNA profiles associated with biovars were obtained, indicating the existence of intraspecific genetic variability in strains of G. anatis circulating in Peru.